Analisis Produksi Dan Pendapatan Pada Izin Usaha Industri Primer Hasil Hutan Kayu (IUIPHHK) Di Kota Palu Studi Kasus Pada PT. Tatehe Nusa Jaya - Haryono Haryono; Syukur Umar; Erniwati Erniwati (Universitas Tadulako, 2015)
The objectives of this research were to: (1) know out the effect of production variable factors; raw materials (m³), labor, and production tools of wood processing. (2) to calculate the production income, and (3) to state the feasibility level of PT. Tatehe Nusa Jaya in relation to Timber Product Business Industry License in Palu City. This research was carried out for five months, from February to June 2014. The population was the duration of sawn timber processing activities at PT. Tatehe Nusa Jaya (36 months). The sample was taken monthly. Then sawn timber processing revenue was affected by the fixed costs, variable costs and revenues. Cobb-Douglass analysis production function was used to answer the problem statement of this research. This research uses qualitative descriptive design. The results of production function showed that coefficient determination was 0.828. It means that the model was effective to be applied since the ability to explain the Y factor in the changes of Xi variables (X1, X2, and X3) was 82.8% or high. Meanwhile, the remaining 17.2% was caused by external factors which was not observed in this research. The operating timber product business industry revenues of PT. Tatehe Nusa Jaya was profitable. The company's revenue was Rp. 31.772.648.018,-. Variable production factors influence the increase in operating revenues IUIPHHK PT. Tatehe Nusa Jaya. This high revenues was taken from the small ratio of total production cost in comparison to the total income. Thus economically good to run because the value of the level of feasibility is Rp. 13.74 and because the value of the RC ratio> 1. It means that the feasibility of company was 1: 13,74.